2001
DOI: 10.1080/02664760120047906
|View full text |Cite
|
Sign up to set email alerts
|

The use of the ARDL approach in estimating virtual exchange rates in India

Abstract: This paper applies the autoregressive distributed lag approach to cointegration analysis in estimating the 'virtual exchange rate' (VER) in India. The VER would have prevailed if the unconstrained import demand were equal to the constraint imposed due to foreign exchange rationing and the VER is used to approximate the 'price' of rationed foreign exchange reserves. We highlight the shortcomings of the existing literature in approximating equilibrium exchange rates in a less developed country such as India and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
163
0
4

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 274 publications
(167 citation statements)
references
References 17 publications
0
163
0
4
Order By: Relevance
“…The order of any series in the ARDL methodology is only needed to identify the critical values for purposes of inference. Second, with the ARDL method it is possible to determine more efficient cointegrating relationship(s) than in the other methods, even if the sample size is very small (Ghatak and Siddiki, 2001). A third advantage is that an error-correction model can be derived through a simple linear transformation.…”
Section: Empirical Model and Resultsmentioning
confidence: 99%
“…The order of any series in the ARDL methodology is only needed to identify the critical values for purposes of inference. Second, with the ARDL method it is possible to determine more efficient cointegrating relationship(s) than in the other methods, even if the sample size is very small (Ghatak and Siddiki, 2001). A third advantage is that an error-correction model can be derived through a simple linear transformation.…”
Section: Empirical Model and Resultsmentioning
confidence: 99%
“…See also; Rafindadi and Ozturk (2015) and Rafindadi and Yusof (2015). See also Rafindadi (2014a;2014b) and Rafindadi (2016a;2016b;2016c): 1 In the first instance, Ghatak and Siddiki (2001). established that a reasonable sample is needed for the sake of comparing it with Johansen cointegration technique.…”
Section: Model Estimation Proceduresmentioning
confidence: 99%
“…This approach has advantages over the other alternatives, Engle and Granger (19) and Johansen (20,21). First, it produces more reliable estimates for small samples than other approaches (22). Second, it does not require all variables used in the analysis have the same order of integration.…”
Section: The Results Of the Ardl/bounds Testmentioning
confidence: 99%
“…Bilgic and Yen (5) and Armağan and Akbay (6) reported that the price elasticities of demand for beef are -1.59 and -1. 22, respectively.…”
Section: Introductionmentioning
confidence: 99%